Introduction of the UNESCO World Heritage Convention at institutional level and on legal terms. The Hungarian example - Harlov-Csortán , Melinda (Protection of Cultural Heritage, 2023)
The text analyses the introduction of the supranational notion of cultural heritage together with the related processes (heritagization) at the Hungarian legal- and institutional level. First, the national governing powers and the legislative texts are analysed in order to find out the named processes on macro level. Then the connecting professional and scientific disciplines (monument-, environment protection and ethnography) are investigated through the institutional structures and their realization steps as well to decode their transformations to cultural heritage on national level. The research focuses on the period between the mid-20th century and the early 2010s, as during this period the international and scientific usage of the term cultural heritage got fully customized in the Hungarian context.